Answer:
u = 3/4
Explanation:
Solve for u:
-5 (6 - 4 u) - 6 u = 6 (u - 3) - 6
-5 (6 - 4 u) = 20 u - 30:
20 u - 30 - 6 u = 6 (u - 3) - 6
Grouping like terms, 20 u - 6 u - 30 = (20 u - 6 u) - 30:
(20 u - 6 u) - 30 = 6 (u - 3) - 6
20 u - 6 u = 14 u:
14 u - 30 = 6 (u - 3) - 6
6 (u - 3) = 6 u - 18:
14 u - 30 = 6 u - 18 - 6
Grouping like terms, 6 u - 18 - 6 = 6 u + (-18 - 6):
14 u - 30 = 6 u + (-18 - 6)
-18 - 6 = -24:
14 u - 30 = 6 u + -24
Subtract 6 u from both sides:
(14 u - 6 u) - 30 = (6 u - 6 u) - 24
14 u - 6 u = 8 u:
8 u - 30 = (6 u - 6 u) - 24
6 u - 6 u = 0:
8 u - 30 = -24
Add 30 to both sides:
8 u + (30 - 30) = 30 - 24
30 - 30 = 0:
8 u = 30 - 24
30 - 24 = 6:
8 u = 6
Divide both sides of 8 u = 6 by 8:
(8 u)/8 = 6/8
8/8 = 1:
u = 6/8
The gcd of 6 and 8 is 2, so 6/8 = (2×3)/(2×4) = 2/2×3/4 = 3/4:
Answer: u = 3/4